Elements of Environmental Management - Antweiler, Werner (Book collections on Project MUSE., 2014)
As businesses face an increasing array of environmental challenges, including climate change, air and water pollution, and solid waste management, environmental management has become an increasingly important area of expertise. Elements of Environmental Management is an interdisciplinary textbook for students and business professionals that integrates corporate environmental strategy with environmental economics, environmental law, and environmental engineering.